2022
DOI: 10.1101/2022.02.07.479393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual coercion in a natural mandrill population

Abstract: Increasing evidence indicates that sexual coercion is widespread. While some coercive strategies are conspicuous, such as forced copulation or sexual harassment, less is known about the ecology and evolution of intimidation, where repeated male aggression promotes future rather than immediate mating success with targeted females. Although known in humans, intimidation was recently reported in chimpanzees and chacma baboons, where males are regularly violent against females. Here, we investigate the nature of m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 84 publications
0
6
1
Order By: Relevance
“…Similarly, the results of our path analysis did not support the 'retaliation' indirect path: female centrality did not predict rank and rank did not mediate the effect of centrality on coercion. Finally, in contrast to previous results 47 (see also Table 3) our path analysis suggested that female rank is not associated with coercion (Table 4), calling for future studies using, for example, more finegrained estimations of female rank, to clarify this association, or lack thereof.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Similarly, the results of our path analysis did not support the 'retaliation' indirect path: female centrality did not predict rank and rank did not mediate the effect of centrality on coercion. Finally, in contrast to previous results 47 (see also Table 3) our path analysis suggested that female rank is not associated with coercion (Table 4), calling for future studies using, for example, more finegrained estimations of female rank, to clarify this association, or lack thereof.…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike hamadryas baboons or bottlenose dolphins, male mandrills rarely, if ever, use overt physical restraint, sequestering or 'herding' behaviors toward females; but they rather coerce females using milder aggressive tactics. 47 While directional grooming of females toward males may be less easily enforced by males than spatial proximity, a recent study in sexually coercive chacma baboons (Papio ursinus) 7 indicates that females may regularly groom males as an appeasement strategy. 56 In mandrills, females have been occasionally observed to groom males after receiving aggression from them (NS personal observation), suggesting that a similar appeasement strategy might explain our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations